Step 1: Distribute to get
2(x−3)+21=−3
2x - 6 + 21 = -3
Step 2: Combine like terms to get
2x + 15 = -3
Step 3: Use
to get 2x = −18
Step 4: Use
to get x = −9
Solve the equation by filling in the steps: 2(x−3)+21=−3
(4 points)
Step 1: Distribute to get
2x - 6 + 21 = -3
Step 2: Combine like terms to get
Step 3: Use
to get 2x=−18
Step 4: Use
to get x=−9
5 answers
for step 3 what do i use to get 2x = -18
Apologies for the confusion in my previous response. To solve for 2x in step 3, you should subtract 15 from both sides of the equation:
2x + 15 = -3
2x + 15 - 15 = -3 - 15
2x = -18
2x + 15 = -3
2x + 15 - 15 = -3 - 15
2x = -18
in step 4 what do i use to get x = -9
To solve for x in Step 4, you need to divide both sides of the equation by 2:
2x = -18
2x/2 = -18/2
x = -9
2x = -18
2x/2 = -18/2
x = -9